ЗЕМЛЕРОБСТВО МАЙЯ ПОСТКЛАСИЧНОГО ПЕРІОДУ (Х-ХVI ст.): ЕКОЛОГІЧНИЙ АСПЕКТ (Zaporizhzhia Historical Review, 2021)
The article deals with forming of the Postclassic Maya agricultural system in a context of geologicclimatic conditions of Yucatan peninsula. Extensive and intensive agronomic methods are picked out, the Mayan strategy of mixed land tenure is figured, the main kinds of household plants briefly reviewed. It is considered, that Mayan agriculture is had to be understood as a part of the complete evolutional system of composing social and ecological processes.